Treści kształcenia z zakresu mechatroniki samochodowej w nauczaniu-uczeniu się studentów kierunku mechatronika - Krupa, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
W artykule zawarto charakterystykę treści kształcenia przedmiotu mechatronika samochodowa w nauczaniu-uczeniu się studentów kierunku mechatronika na Uniwersytecie Rzeszowskim ze szczególnym uwzględnieniem zagadnień realizowanych na zajęciach wykładowych.

The article includes the description of educational content of mechatronics car subject, when it comes to the teaching of students of Mechatronics at the University of Rzeszów, with special emphasis on the activities carried out on lectures.
The content of education in the field of automotive mechatronics in the teaching-learning students of mechatronics
Keywords: mechatronika; mechatronika samochodowa; treści kształcenia; sensory; aktuatory; mechatronics; automotive mechatronics; educational content; sensors; actuators